Análise da composição química e da atividade antibacteriana e antifúngica de clones de Schinus terebinthifolia Raddi - Moraes, Rodrigo (2023)
Aroeira (Schinus terebinthifolia Raddi) is included in the Brazilian List of Essential Medicines due to its potential to generate bioactive compounds, including those with antimicrobial properties. The occurrence of antimicrobial resistance increases health care costs, length of stay in hospitals, morbidity, and mortality. WHO has published a list of antibiotic-resistant “priority pathogens” to guide and promote research, development, and innovation of new antibiotics including those that may combat oxacillin-resistant Staphylococcus aureus and carbapenemase-producing Klebsiella pneumoniae. Fungi of the genus Fusarium are important pathogens for plants, humans, and animals, in addition to producing mycotoxins in food, with a great lack of new molecules that can be used for their control. This research sought to characterize the phytochemical profile of polar and non-polar extracts of mature fruits of four Aroeira clones and their antimicrobial activity against oxaxilin-resistant Staphylococcus aureus, carbapenemase-producing Klebsiella pneumoniae and the fungus Fusarium guttiforme. The extracts of all aroeira clones showed antimicrobial activity for bacteria and fungus, varying according to the clone and solvent used. Polar extracts showed greater antifungal and antibacterial activity, being more active on Gram-positive bacteria. The antifungal and antibacterial activity varied according to the evaluated clone. Clone BAAr 5 showed greater antibacterial activity while clones BAAr 5 and BAAr 8 had greater antifungal activity. The Aroeira clones showed similarity in the chromatographic profile by HPLC. It was possible to observe a greater relative number of peaks in clone BAAr 5 when extracted using a hydroethanolic solvent. The chromatogram of the hexane extracts showed a greater diversity of peaks. There was a greater abundance of sesquiterpenes compared to monoterpenes when the samples were evaluated in GC-MS. Spectrometry using ESI(-)FT-ICR MS identified the presence of 29 ions, between m/z 195 and m/z 925 in the polar extracts of the clones. Twenty-four ions were observed in clone BAAr 5, 20 in clone BAAr 8, 23 in clone BAAr9 and 17 in clone BAAr 23. Although the clones were grown under the same edaphoclimatic conditions, they showed variation in antimicrobial activity and bioactive compounds identified. It is suggested that the commercial use of Aroeira should come from selected and cloned plants that present the desired characteristics